Distribution of heavy minerals sand in Namalope deposit, Moma district, Mozambique - Assane, Ali Ossufo (Rhodes University, Faculty of Science, Department of Geology, 2014)
The spatial distribution of heavy minerals along the mine paths 2014 and 2015 at the wet concentrate plant B shows an increase of heavy minerals sand concentration northwards and slime contents southwards, and it is commonly associated with depth and grain sorting; the increase of heavy minerals concentration with depth is considered to be from the surface formed by Unit 6 to the bottom of Unit 7. The Unit 82 is characterized by low heavy minerals concentrations and high slime contents declining northwards. The mineral proportion estimation suggests that ilmenite is the most abundant heavy mineral in the entire area followed by zircon, rutile and mozanite, and some accessory minerals such as chromite, kyanite, staurolite, tourmaline, epidote, spinel and quartz. The ilmenite occurrence is divided into ilmenite low (< 53% TiOâ‚‚) and high (> 53% TiOâ‚‚); the ilmenite high with zircon and rutile shows tendency to increase northwards while ilmenite low increase southwards. Zircon, monazite, rutile, chromite, kyanite and staurolite show low variability, which is probably associated with high resistance of minerals for abrasion during transportation and diagenesis. The depositional model of the Namalope deposit, in the flat area and wet concentrate plant B in particular, suggests deposition in a shallow marine environment associated with regression for deposition of Unit 6, 7 and 9 and transgression during deposition of Unit 82. The spatial distribution of heavy minerals in the Namalope deposit and its environment of deposition are the key points for discovery of new deposits around the Namalope with the same characteristic of mineral assemblage and they are used for mine strategic plans such as update block model and mine design.
Keywords: Heavy minerals -- Mozambique -- Moma District; Prospecting -- Mozambique -- Moma District; Mines and mineral resources -- Mozambique -- Moma District; Ilmenite -- Research; Zircon -- Research; Rutile -- Research